Usefulness of Longitudinal Strain to Assess Cancer Therapy-Related Cardiac Dysfunction and Immune Checkpoint Inhibitor-Induced Myocarditis - Yudai Tamura; Yuichi Tamura (Pharmaceuticals, 2023)
Longitudinal strain (LS) measured by echocardiography has been reported to be useful not only for the diagnosis and risk stratification of various cardiac diseases, but also in cardio-oncology. Most previous studies have been conducted on patients undergoing treatment with anthracyclines and human epidermal growth factor receptor 2-targeted therapies. Existing guidelines recommend that global LS (GLS) should be measured before and after the administration of cancer drugs. This recommendation is based on many reports showing that a decline in GLS is indicative of early or mild cancer therapy-related cardiac dysfunction. The main purpose of this article is to provide insight into the importance of LS in patients undergoing cancer treatment and highlight the role of LS evaluation in patients undergoing immune checkpoint inhibitor (ICI) treatment, which is being used with increasing frequency. Among cancer drug therapies, immune checkpoint inhibitors (ICIs) have an important place in cancer treatment and are used for the treatment of many types of cancer. Although the efficacy of ICIs in cancer treatment has been reported, immune-related adverse events (irAEs) have also been reported. Among these irAEs, cardiovascular complications, although rare, are recognized as important adverse events that may result in ICI treatment discontinuation. Myocarditis is one severe adverse event associated with ICIs, and it is important to standardize diagnostic and therapeutic approaches to it. Several studies have reported a relationship between LS and cardiac complications associated with ICIs which may contribute to the early diagnosis of ICI-induced cardiac complications.